Avant-garde gestures and contemporaneity in today’s circus (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
Contemporary circus, drawing on traditional practices, apparatuses, and a number of their spectacular conventions, emphasises the performance of exceptional human acrobatic feats, ingenuity, or spectacular, often counter-intuitive inventiveness. The contemporary is not necessarily of the avant-garde, but defining the contours and ethos of circus’s contemporaneity help explore its manifestations of the avant-garde. There are examples on the edges, where circus and dance, burlesque, performance art, non-acting and political engagement coexist. Most of the avant-garde practices are featured at international festivals. They are not outside of the norms, they actually set them. This chapter explores the intersection and, at times, complicated cohabitation between conception of the contemporary and of the avant-garde in current circus practice and reception. It first defines and contextualises contemporaneity in today’s circus, then proposes a dialectics of contemporary circus and concludes with enactments of the avant-garde and how they relate to our current understanding of circus.
Keywords: Contemporary circus; Avant-garde; History of circus; New circus practices